Retinoblastoma Extending up to the Optic Chiasma and Presenting as a Suprasellar Mass - Mishra, Himanshu; Kumar, Amit (Nepal Journal of Neuroscience, 2021)
Retinoblastoma is the most common ocular malignancy of childhood. It is present in childhood with leukocoria and strabismus. Most patients are diagnosed under 3 years of age. Funduscopic examination can reveal an intraocular mass, but imaging is essential for complete evaluation of the lesion. Although ultrasound is a non-invasive and relatively inexpensive screening tool, cross-sectional imaging is required to assess the involvement of optic nerve and intracranial spread. We report a case of retinoblastoma in a 5 year old male child who presented with headache diminution of vision in both eyes. Contrast enhanced magnetic resonance imaging (MRI) revealed an enhancing soft tissue mass in the right eye with involvement of optic nerve and optic chiasma and contiguous with a large suprasellar mass causing hydrocephalus. Non-contrast computed tomography (CT) showed extensive calcifications in the mass lesion.